Changes in bacterial and eukaryotic communities during sewage decomposition in Mississippi river water. (1st February 2015) - Korajkic, Asja; Parfrey, Laura Wegener; McMinn, Brian R.; Baeza, Yoshiki Vazquez; VanTeuren, Will; Knight, Rob; Shanks, Orin C.
Abstract: Microbial decay processes are one of the mechanisms whereby sewage contamination is reduced in the environment. This decomposition process involves a highly complex array of bacterial and eukaryotic communities from both sewage and ambient waters. However, relatively little is known about how these communities change due to mixing and subsequent decomposition of the sewage contaminant. We investigated decay of sewage in upper Mississippi River using Illumina sequencing of 16S and 18S rRNA gene hypervariable regions and qPCR for human-associated and general fecal Bacteroidales indicators. Mixtures of primary treated sewage and river water were placed in dialysis bags and incubated in situ under ambient conditions for seven days. We assessed changes in microbial community composition under two treatments in a replicated factorial design: sunlight exposure versus shaded and presence versus absence of native river microbiota. Initial diversity was higher in sewage compared to river water for 16S sequences, but the reverse was observed for 18S sequences. Both treatments significantly shifted community composition for eukaryotes and bacteria ( P < 0.05). Data indicated that the presence of native river microbiota, rather than exposure to sunlight, accounted for the majority of variation between treatments for both 16S ( R = 0.50; P > 0.001) and 18S ( R = 0.91; P = 0.001) communities. A comparison of 16S sequence data and fecal indicator qPCR measurements indicated that the latter was a good predictor of overall bacterial community change over time (rho: 0.804–0.814, P = 0.001). These findings suggest that biotic interactions, such as predation by bacterivorous protozoa, can be critical factors in the decomposition of sewage in freshwater habitats and support the use of Bacteroidales genetic markers as indicators of fecal pollution. Graphical abstract: Highlights: River microbiota are important contributors to the decomposition of sewage-derived organisms. Several bacteria and eukaryote groups exhibited bloom and die-off trends. After seven days of decomposition, most sewage associated bacteria were undetectable. Bacteroidales qPCR measurements are good predictors of bacterial community shifts.